Do fracasso à reforma das operações de paz das Nações Unidas (2000-2010) - Bigatão, Juliana de Paula [UNESP] (2015)
The study analyzes the United Nations (UN) Peace Operations reform, which started in 2000 with the publication of the Brahimi Report, establishing new guidelines to strengthen peace operations after the failures in Rwanda, Bosnia Herzegovina and Somalia in the mid-1990s. The purpose is to understand the consequences of the reform to the conception of peace that guided UN missions and the way in which the UN Security Council has translated this conception into the interventions design during the decade that followed the publication of the Report. The hypothesis that guided this research was that there is a gap between the conception of peace - sustainable peace resulting from dealing with conflict causes - and the design of the intervention - robust peacekeeping followed by peacebuilding activities - because the UN peacekeeping operations are driven by two main factors. The first relates to the fact that, in the political process which precedes the intervention approval, there is a preponderance of the outsiders perspective, of the way that the external forces perceives the conflict, deciding the role of the missions; besides, there is a standardized model to respond to different types of conflicts. The second factor is that peace operations respond to conflict to the extent that there are resources for the implementation of the mandates and within specific conditions determined by the warring groups, which need to consent, at least formally, the presence of external actors to manage the transition to peace. ...